2019
DOI: 10.1007/s13197-019-03602-2
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of viscoelastic behaviour of rice-field bean gluten-free dough using the biophysical characterization of proteins and starch: a FT-IR study

Abstract: Gluten-free bread making success is closely linked to the biophysical behaviour of dough. Quality of these doughs is largely determined by the properties of their proteins and starch. This study aimed to explain, at the structural level the rheological behaviour of gluten-free rice-field bean dough compared to that of soft wheat. The conformational aspects of proteins and starch were studied using Fourier transformed infrared spectroscopy (FT-IR). Doughs of soft wheat, rice, field bean, mixture of rice-field b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 34 publications
0
15
0
1
Order By: Relevance
“…The composition of secondary protein structure participating in the amide I band was expressed as a percentage of the area of the fitted region denoted as a relative area of components centered at specific wavenumbers [Bock & Damodaran, 2013]. The secondary structure assignment was based on absorption wavenumbers as described previously [Fetouhi et al, 2019]. Amide I secondary structures: α-helix (1649-1659 cm -1 ), β-sheet (1620-1644 cm -1 ), β-turn (1660-1688 cm -1 ), and random coils (1510-1619 cm -1 ) were assigned.…”
Section: Ftir Analysis and Data Manipulationmentioning
confidence: 99%
See 1 more Smart Citation
“…The composition of secondary protein structure participating in the amide I band was expressed as a percentage of the area of the fitted region denoted as a relative area of components centered at specific wavenumbers [Bock & Damodaran, 2013]. The secondary structure assignment was based on absorption wavenumbers as described previously [Fetouhi et al, 2019]. Amide I secondary structures: α-helix (1649-1659 cm -1 ), β-sheet (1620-1644 cm -1 ), β-turn (1660-1688 cm -1 ), and random coils (1510-1619 cm -1 ) were assigned.…”
Section: Ftir Analysis and Data Manipulationmentioning
confidence: 99%
“…In analyzing gluten-free cake, Fetouhi et al [2019] obtained the R-ratio between 0.6 and 0.8 and concluded that its high values indicated a high tendency of starch for retrogradation [Fetouhi et al, 2019].…”
Section: Analysis Of Starch Conformationmentioning
confidence: 99%
“…Maltodekstrin sebagai produk modifikasi pati sedangkan natrium kaseinat merupakan protein susu yang banyak digunakan sebagai pengemulsi, keduanya berperan besar dalam penentuan sifat viskoelastisitas emulsi dari mikrokapsul. Sebagaimana yang dinyatakan Fetouhi et al (2019) wa protein merupakan komponen utama yang bertanggungjawab dalam sifat viskoelastis dalam produk pangan yang berbasis campuran protein dan pati. Penambahan protein dalam komposisinya dengan pati/polisakarida dapat meningkatkan sifat-sifat viskoelastis yang sangat besar pada produk pasta atau gel.…”
Section: Hasil Dan Pembahasan Viskositas Dan Rendemen Mikrokapsulunclassified
“…Vibrational spectroscopy such as infrared (IR), near-infrared (NIR), and Raman spectroscopy are sensitive to changes in the internal structure of polymetric materials, including biological materials. [19][20][21][22][23][24][25] Numerous studies have been carried out regarding not only changes in the crystallinity of starch in rice flour during processing but also those in its chain conformation, and helicity and local structure by vibrational spectroscopy often combined with wide-angle X-ray diffraction. 25,26 Specifically, FT-IR has been used extensively to quantify the short-range order as a crystalline phase index of starchy materials.…”
Section: Introductionmentioning
confidence: 99%